Dynamic and vibration analysis of a quadrotor type with a payload: insights for aerial medical product transportation - Geronel, Renan Sanches (2023)
Unmanned Aerial Vehicles (UAVs) have gained rapid attention as a potential solution to overcome geographical and logistic challenges in different areas. In particular for medical and hospital products transportation, UAVs are used to assist health care services in the delivery of medical goods, including organs, vaccines and blood samples. However, some of these products are sensitive to vibration, which can decrease the therapeutic efficacy of the transported payload. Then, this thesis investigates the vibration characteristics of a payload carried by a quadrotor. A commercial UAV is used to evaluate the effect of the payload dynamics on the flight, by considering different attachment configurations. The results have shown an amplification of the quadrotor acceleration, highlighting the importance of controlling these vibrating effects. Regarding the dynamic models, a vertical vibrating payload is initially investigated, by assessing two different control strategies (quasi-open and closed loops). The combination of elastic attachment and suspended payload have been assessed. The Adaptive Sliding Mode Control have been designed to compensate the payload effects on the UAV dynamics. Therefore, oscillations caused by an attached mass, external disturbances and different dynamic configurations have become and important topic in UAV medical transportation. Low payload oscillations may guarantee a rapid spread and use of commercial UAVs for medical products delivery, with a high transportation reliability.